International review of cytology : a survey of cell biology - Jeon, Kwang W. (International review of cytology, 2006)
International Review of Cytology presents current advances and comprehensive reviews in cell biology - both plant and animal. Authored by some of the foremost scientists in the field, each volume provides up-to-date information and directions for future research. Articles in this volume address endogenous ligands of PACAP, VIP receptors in the autocrine-paracrine regulation of the adrenal gland; ultrastructural dynamcs of human reproduction, from ovulation to fertilization and early embryo development; chromosomal variation in mammalian neuronal cells; automated interpretation of protein subcellular location patterns; cell and molecular biology of human lacrimal gland and nasolacrimal duct mucins.